Changes in the Pattern of Bikeshare Usage due to the COVID-19 Pandemic - Haoyun Wang; Robert Noland (Findings)
Bikeshare use in New York City dropped substantially during the initial months of the COVID-19 pandemic, but by summer of 2020 had largely recovered to pre-pandemic levels. The patterns of usage, however, have changed. In this study we compare bikeshare trip patterns in September 2020 to September 2019, restricting our analysis to the Borough of Brooklyn in New York City. We focus on user types, time of day, and changes in the origin and destination of trips, based on aggregated land uses surrounding docking stations. Our results suggest a shift toward longer trips and more recreational trips with fewer work-related trips.